Monetary policy, capital flows and exchange rates : essays in memory of Maxwell Fry - Dickinson, David G.; Allen, Bill (London : Routledge, 2002)
This collection has been brought together in honour of the late economist Maxwell Fry. It contains state-of-the-art articles on monetary and exchange rate policy, capital flows, currency markets and exchange rate policies. It includes contributions from Charles Goodhart and Gerry Caprio, as well as a foreword from Eddie George, the governor of the Bank of England.
Includes bibliographical references and index.
oif 29/07/15
Loan
Keywords: Fry, Maxwell J; Monetary policy; Capital movements; Foreign exchange rates